Polarization-maintaining optical waveguide and manufacturing method thereof
Through a two-stage ion exchange process, the birefringent core layer and stress zone are formed on the glass substrate, which solves the problems of high difficulty in polarization-maintaining waveguide process and poor matching with optical fiber in the prior art, and achieves low coupling loss and high polarization extinction The effect of comparison.
Patent Information
- Application Number
- CN202411408225.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2024-12-20
AI Technical Summary
The existing polarization-maintaining waveguides are difficult to manufacture, costly and poorly matched with optical fibers, resulting in bottlenecks in application scenarios with high extinction ratio requirements.
Using a two-stage ion exchange process, the core layer and stress region with birefringence effect are formed by coating, photolithography, etching and electric field-assisted ion exchange on the glass substrate, thereby achieving low coupling loss and high polarization extinction ratio.
It reduces the difficulty of making optical waveguides, achieves good matching with optical fibers, and improves the polarization retention effect, which has better performance than non-polarized waveguides.
Smart Images

Figure CN119165582A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a polarization-maintaining optical waveguide and the field of integrated optics, and in particular to a polarization-maintaining optical waveguide and a manufacturing method thereof. Background Art
[0002] With the development of the market and technology, the application of polarization-maintaining optical fiber tends to grow rapidly with the maturity of polarization-maintaining optical fiber technology and the decline in cost, while optical waveguide components that match polarization-maintaining optical fiber are still in the early stages of development. The cost of polarization-maintaining optical fiber components made of fused tapers is high due to the high difficulty in production; in the past development of planar optical waveguide components, there have been related studies on polarization-maintaining optical waveguides, but their production process requirements are high, and the matching with polarization-maintaining optical fiber is poor, and there are currently no mature products for the market. The use of non-polarization-maintaining planar optical waveguide components with low polarization-dependent loss is a common solution currently adopted in the market, but this solution has bottlenecks in application scenarios with high extinction ratio requirements. Summary of the invention
[0003] In order to solve the problems existing in the background technology, the present invention provides a polarization-maintaining optical waveguide and a method for manufacturing the same. The purpose of the present invention is to reduce the process difficulty of the polarization optical waveguide, achieve low coupling loss with the optical fiber, and maintain a high polarization extinction ratio.
[0004] The technical solution adopted by the present invention is:
[0005] 1. A method for manufacturing a polarization-maintaining optical waveguide:
[0006] S1: performing a first coating, photolithography, a first etching and a first thermal ion exchange in sequence on the upper surface of the glass substrate to form a stress region in an initial state.
[0007] S2: performing a first electric field-assisted ion exchange on the upper surface of the glass substrate to form an intermediate stress region.
[0008] S3: performing a second coating, overlay, a second etching and a second thermal ion exchange in sequence on the upper surface of the glass substrate to form a core layer in an initial state.
[0009] S4: A second electric field-assisted ion exchange is performed on the upper surface of the glass substrate to form a stress region in a final state, a core layer in a final state and a cladding layer thereon, thereby completing the production of a polarization-maintaining optical waveguide.
[0010] In the step S1, the upper surface of the glass substrate is firstly plated using a first mask, and then the first mask is sequentially subjected to coating, pre-baking, photolithography, development and post-baking, thereby forming a photoresist layer with a first design pattern on the first mask, and there is no photoresist in the area of the first design pattern; then the photoresist layer is first etched to remove the photoresist layer located in the area of the first design pattern and the first mask directly thereunder, thereby exposing the glass substrate directly thereunder, and then the photoresist layer on the first mask is completely removed to form a glass substrate with a mask; a first mask for a membrane window; laying a layer of a first thermal ion exchange molten salt on the first mask with a mask window, the first thermal ion exchange molten salt completely filling the mask window, and then performing thermal ion exchange, thereby forming a stress zone with a semicircular cross-section in an initial state on a glass substrate and its surrounding area directly below the mask window, and finally removing the first mask on the upper surface of the glass substrate; the first design pattern includes two strips symmetrical to the center line of the upper surface of the glass substrate, and stress zones are formed on the glass substrate and its surrounding area directly below each strip, and the stress zones are symmetrically distributed on both sides of the central cross-section of the glass substrate.
[0011] In the step S2, first, an electric field-assisted ion exchange power supply is prepared, and the electric field-assisted ion exchange power supply includes two electric field-assisted ion exchange electrode plates containing electric field-assisted ion exchange molten salt. The two electric field-assisted ion exchange electrode plates are respectively placed on the upper and lower surfaces of the glass substrate, and the first electric field-assisted ion exchange is performed after power is turned on, thereby forming a stress zone in an intermediate state with a cross-sectional radius larger than the stress zone in the initial state, and finally the two electric field-assisted ion exchange electrode plates are removed.
[0012] In the step S3, firstly, a second coating is performed on the upper surface of the glass substrate with the stress zone in the intermediate state using a second mask, and then the second mask is sequentially subjected to coating, pre-baking, overlaying, developing and post-baking, thereby forming a photoresist layer with a second design pattern on the second mask, and there is no photoresist in the area of the second design pattern. When overlaying, the second mask needs to be aligned with the photolithography so that the center of the second mask is located at the center of the two stress zones; then the same etching and thermal ion exchange process as in step S1 is performed, and when the second thermal ion exchange is performed, a second thermal ion exchange molten salt is used, and finally a core layer with a semicircular cross-section in the initial state is formed on the glass substrate directly below the mask window and its surrounding area, and finally the second mask on the upper surface of the glass substrate is removed; the second design pattern is strip-shaped, and the two strips of the first design pattern are symmetrical to the strips of the second design pattern.
[0013] In the step S4, the glass substrate containing the stress zone in the intermediate state and the core layer in the initial state is subjected to the same electric field assisted ion exchange as in step S2, thereby forming a stress zone in the final state having a cross-sectional radius greater than that of the stress zone in the intermediate state and a core layer in the final state having a cross-sectional radius greater than that of the core layer in the initial state, the upper surface of the stress zone in the final state and the upper surface of the glass substrate are located on the same plane, the upper surface of the core layer in the final state is located directly below the upper surface of the glass substrate and are parallel to each other, the glass substrate directly above the core layer in the final state is the cladding, and finally the two electric field assisted ion exchange electrode plates are removed, and the glass substrate left above the core layer due to burying constitutes the cladding.
[0014] In the step S4, the diameter of the stress zone in the final state is 10 to 100 μm, and the diameter of the core layer in the final state is 5 to 8 μm; the center distance between the stress zone in the final state and the core layer in the final state is greater than the sum of the radius of the core layer in the final state and the radius of the stress zone in the final state plus 10 μm, and the center distance between the stress zone in the final state and the core layer in the final state ranges from 18 to 75 μm; the thickness of the cladding is 0.5 to 2 μm.
[0015] In the step S4, the refractive index of the core layer in the final state is greater than the refractive index of the stress region in the final state.
[0016] In the steps S1 and S2, the source ions of the first thermal ion exchange are Li + or K + The first thermal ion exchange time is 8 to 96 hours; the first electric field assisted exchange time is 3 to 10 minutes.
[0017] In the steps S3 and S4, the source ions of the second thermal ion exchange are Ag. + or Tl + The thermal ion exchange time is 5 to 30 minutes; the second electric field assisted exchange time is 15 to 120 minutes.
[0018] 2. A polarization-maintaining waveguide:
[0019] The polarization-maintaining optical waveguide is prepared by the method described above.
[0020] The present invention adopts a two-stage ion exchange process to realize the production of polarization-maintaining optical waveguides, and the process difficulty is relatively low and the implementation is relatively simple. The implementation principle is that firstly, long-term high-concentration ion exchange generates compressive stress in the stress zone, thereby realizing the horizontal extrusion of the optical waveguide core layer; secondly, there is no force structure in the vertical direction of the optical waveguide core layer, so that the core layer produces birefringence, and the optical waveguide maintains the polarized light, which is similar to the principle of polarization-maintaining optical fiber. In addition, considering that the refractive index difference generated in the stress zone should be smaller than the refractive index difference of the core layer to avoid light coupling and leakage, the stress zone selects source ions with low refractive index difference and stress structure, while the core layer selects source ions with high refractive index difference and low stress, and the process is also coordinated accordingly.
[0021] The beneficial effects of the present invention are:
[0022] The present invention adopts a two-stage ion exchange process, and the manufacturing difficulty is relatively low; at the same time, the optical waveguide and the optical fiber can achieve good matching; compared with the non-polarization-maintaining optical waveguide, it has a better polarization maintaining effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 is a cross-sectional schematic diagram of a polarization-maintaining optical waveguide;
[0024] Figure 2 A schematic diagram of a process for manufacturing a polarization-maintaining optical waveguide;
[0025] In the figure, 1. glass substrate, 2. stress zone, 3. core layer, 4. cladding, 11. mask, 12. mask window, 13. first thermal ion exchange molten salt, 14. electric field assisted ion exchange molten salt, 15. electric field assisted ion exchange electrode plate, 16. electric field assisted ion exchange power supply, 17. second thermal ion exchange molten salt. DETAILED DESCRIPTION
[0026] The present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0027] like Figure 2 As shown, the specific implementation process of the present invention is as follows:
[0028] Embodiment 1:
[0029] First, the upper surface of the glass substrate 1 is subjected to coating, photolithography, etching, and the first thermal ion exchange to form the stress zone 2 in the initial state; the glass substrate 1 containing the stress zone 2 in the initial state is subjected to the first electric field assisted ion exchange to form the stress zone 2 in the intermediate state; the upper surface of the glass substrate 1 containing the stress zone 2 in the intermediate state is subjected to coating, overlay, etching, and the second thermal ion exchange to form the core layer 3 in the initial state; the glass substrate 1 containing the core layer 3 in the initial state is subjected to the second electric field assisted ion exchange to form the stress zone 2 and the core layer 3 in the final state, and the glass substrate left above the core layer 3 due to burial constitutes the cladding 4. The source ion of the first thermal ion exchange is Li + In the mixed molten salt of lithium nitrate and sodium nitrate, the concentration of lithium nitrate is 10%, the thermal ion exchange temperature is 400℃, and the exchange time is 8h; the source ion of the second thermal ion exchange is Ag. + In the mixed molten salt of silver nitrate, sodium nitrate and calcium nitrate, the concentration of silver nitrate is 1‰, the thermal ion exchange temperature is 320℃, and the exchange time is 5min; the voltage of the first electric field assisted exchange is 300V, and the time is 3min; the voltage of the second electric field assisted exchange is 330V, and the time is 15min.
[0030] The final polarization-maintaining waveguide is as follows: Figure 1 As shown, the diameter of the stress zone 2 is 10 μm, the diameter of the core layer 3 is 5 μm, the center distance between the core layer 3 and the stress zone 2 is 18 μm, and the thickness of the cladding 4 is 0.5 μm; the refractive index of the core layer 3 obtained by the process is 1.521, and the refractive index of the stress zone 2 is 1.507.
[0031] Embodiment 2:
[0032] First, the upper surface of the glass substrate 1 is subjected to coating, photolithography, etching, and the first thermal ion exchange to form the stress zone 2 in the initial state; the glass substrate 1 containing the stress zone 2 in the initial state is subjected to the first electric field assisted ion exchange to form the stress zone 2 in the intermediate state; the upper surface of the glass substrate 1 containing the stress zone 2 in the intermediate state is subjected to coating, overlay, etching, and the second thermal ion exchange to form the core layer 3 in the initial state; the glass substrate 1 containing the core layer 3 in the initial state is subjected to the second electric field assisted ion exchange to form the stress zone 2 and the core layer 3 in the final state, and the glass substrate left above the core layer 3 due to burial constitutes the cladding 4. The source ion of the first thermal ion exchange is K + In the mixed molten salt of potassium nitrate and sodium nitrate, the concentration of potassium nitrate is 50%, the thermal ion exchange temperature is 380℃, and the exchange time is 96h; the source ion of the second thermal ion exchange is Tl +In the mixed molten salt of thallium nitrate, potassium nitrate and sodium nitrate, the concentration of thallium nitrate is 0.5‰, the thermal ion exchange temperature is 260℃, and the exchange time is 30min; the voltage of the first electric field assisted exchange is 180V, and the time is 10min; the voltage of the second electric field assisted exchange is 280V, and the time is 120min.
[0033] The diameter of the stress zone 2 finally obtained is 100μm, the diameter of the core layer 3 is 8μm, the center distance between the core layer 3 and the stress zone 2 is 75μm, and the thickness of the cladding 4 is 2μm; the refractive index of the core layer 3 obtained by the process is 1.512, and the refractive index of the stress zone 2 is 1.510.
[0034] Embodiment 3:
[0035] First, the upper surface of the glass substrate 1 is subjected to coating, photolithography, etching, and the first thermal ion exchange to form the stress zone 2 in the initial state; the glass substrate 1 containing the stress zone 2 in the initial state is subjected to the first electric field assisted ion exchange to form the stress zone 2 in the intermediate state; the upper surface of the glass substrate 1 containing the stress zone 2 in the intermediate state is subjected to coating, overlay, etching, and the second thermal ion exchange to form the core layer 3 in the initial state; the glass substrate 1 containing the core layer 3 in the initial state is subjected to the second electric field assisted ion exchange to form the stress zone 2 and the core layer 3 in the final state, and the glass substrate left above the core layer 3 due to burial constitutes the cladding 4. The source ion of the first thermal ion exchange is K + In the mixed molten salt of potassium nitrate and sodium nitrate, the concentration of potassium nitrate is 25%, the thermal ion exchange temperature is 410℃, and the exchange time is 48h; the source ion of the second thermal ion exchange is Ag. + In the mixed molten salt of silver nitrate, sodium nitrate and calcium nitrate, the concentration of silver nitrate is 0.8‰, the thermal ion exchange temperature is 280℃, and the exchange time is 15min; the voltage of the first electric field assisted exchange is 220V, and the time is 7min; the voltage of the second electric field assisted exchange is 350V, and the time is 90min.
[0036] The final stress zone 2 has a diameter of 50 μm, the core layer 3 has a diameter of 6.5 μm, the center distance between the core layer 3 and the stress zone 2 is 60 μm, and the cladding 4 has a thickness of 1 μm; the refractive index of the core layer 3 obtained by the process is 1.513, and the refractive index of the stress zone 2 is 1.508.
[0037] Embodiment 4:
[0038] First, the upper surface of the glass substrate 1 is subjected to coating, photolithography, etching, and the first thermal ion exchange to form the stress zone 2 in the initial state; the glass substrate 1 containing the stress zone 2 in the initial state is subjected to the first electric field assisted ion exchange to form the stress zone 2 in the intermediate state; the upper surface of the glass substrate 1 containing the stress zone 2 in the intermediate state is subjected to coating, overlay, etching, and the second thermal ion exchange to form the core layer 3 in the initial state; the glass substrate 1 containing the core layer 3 in the initial state is subjected to the second electric field assisted ion exchange to form the stress zone 2 and the core layer 3 in the final state, and the glass substrate left above the core layer 3 due to burial constitutes the cladding 4. The source ion of the first thermal ion exchange is Li + , K + Mixed ions, in which lithium nitrate and potassium nitrate were mixed in a ratio of 1:1, the thermal ion exchange temperature was 375°C, and the exchange time was 16 hours; the source ion of the second thermal ion exchange was Tl + In the mixed molten salt of thallium nitrate and sodium nitrate, the concentration of thallium nitrate is 0.75‰, the thermal ion exchange temperature is 300℃, and the exchange time is 20min; the voltage of the first electric field assisted exchange is 150V, and the time is 7min; the voltage of the second electric field assisted exchange is 420V, and the time is 40min.
[0039] The diameter of the stress zone 2 finally obtained is 35μm, the diameter of the core layer 3 is 7.5μm, the center distance between the core layer 3 and the stress zone 2 is 50μm, and the thickness of the cladding 4 is 0.5μm; the refractive index of the core layer 3 obtained by the process is 1.522, and the refractive index of the stress zone 2 is 1.507.
Claims
1. A method for manufacturing a polarization-maintaining optical waveguide, characterized in that: include: S1: performing a first coating, photolithography, a first etching and a first thermal ion exchange in sequence on the upper surface of the glass substrate (1) to form a stress region (2) in an initial state; S2: performing a first electric field-assisted ion exchange on the upper surface of the glass substrate (1) to form an intermediate stress region (2); S3: performing a second coating, overlay, a second etching and a second thermal ion exchange on the upper surface of the glass substrate (1) in sequence to form a core layer (3) in an initial state; S4: A second electric field-assisted ion exchange is performed on the upper surface of the glass substrate (1) to form a stress region (2) in a final state, a core layer (3) in a final state, and a cladding layer (4) thereon, thereby completing the production of a polarization-maintaining optical waveguide.
2. The method for manufacturing a polarization-maintaining optical waveguide according to claim 1, characterized in that: In the step S1, the upper surface of the glass substrate (1) is firstly plated using a first mask (11), and then coating, pre-baking, photolithography, development and post-baking are sequentially performed on the first mask (11), thereby forming a photoresist layer with a first design pattern on the first mask (11), and no photoresist is present in the area of the first design pattern; Then, a first etching is performed on the photoresist layer to remove the photoresist layer located at the first design pattern area and the first mask (11) directly therebelow by etching, thereby exposing the glass substrate (1) directly therebelow the first design pattern area, and then the photoresist layer on the first mask (11) is completely removed to form a first mask (11) with a mask window (12); a layer of a first thermal ion exchange molten salt (13) is laid on the first mask (11) with the mask window (12), and the first thermal ion exchange molten salt (13) completely fills the mask window A mask window (12) is formed, and then a thermal ion exchange is performed, so that a stress zone (2) in an initial state with a semicircular cross section is formed on the glass substrate (1) directly below the mask window (12) and its surrounding area, and finally the first mask (11) on the upper surface of the glass substrate (1) is removed; the first design pattern includes two strips symmetrical to the center line of the upper surface of the glass substrate (1), and the glass substrate (1) and its surrounding area directly below each strip form a stress zone (2), and the stress zones (2) are symmetrically distributed on both sides of the central cross section of the glass substrate (1).
3. The method for manufacturing a polarization-maintaining optical waveguide according to claim 2, characterized in that: In the step S2, firstly, an electric field assisted ion exchange power source (16) is prepared, the electric field assisted ion exchange power source (16) comprising two electric field assisted ion exchange electrode plates (15) containing electric field assisted ion exchange molten salt (14), the two electric field assisted ion exchange electrode plates (15) are respectively placed on the upper and lower surfaces of the glass substrate (1), and the first electric field assisted ion exchange is performed after power is turned on, thereby forming a stress zone (2) in an intermediate state whose cross-sectional radius is larger than the stress zone (2) in the initial state, and finally the two electric field assisted ion exchange electrode plates (15) are removed.
4. The method for manufacturing a polarization-maintaining optical waveguide according to claim 2, characterized in that: In the step S3, firstly, a second coating is performed on the upper surface of the glass substrate (1) with the stress area (2) in the intermediate state using a second mask, and then coating, pre-baking, overlaying, developing and post-baking are performed in sequence on the second mask, so that a photoresist layer with a second design pattern is formed on the second mask, and there is no photoresist in the area of the second design pattern. When overlaying is performed, the second mask needs to be aligned with the photolithography so that the center of the second mask is located at the center of the two stress areas (2); then the same etching and thermal ion exchange process as in step S1 is performed, and when performing the second thermal ion exchange, a second thermal ion exchange molten salt (17) is used, and finally a core layer (3) in an initial state with a semicircular cross-section is formed on the glass substrate (1) directly below the mask window (12) and its surrounding area, and finally the second mask on the upper surface of the glass substrate (1) is removed; the second design pattern is in the shape of strips, and the two strips of the first design pattern are symmetrical to the strip of the second design pattern.
5. The method for manufacturing a polarization-maintaining optical waveguide according to claim 3, characterized in that: In the step S4, the glass substrate (1) containing the stress zone (2) in the intermediate state and the core layer (3) in the initial state is subjected to the same electric field assisted ion exchange as in step S2, thereby forming a stress zone (2) in the final state having a cross-sectional radius greater than that of the stress zone (2) in the intermediate state and a core layer (3) in the final state having a cross-sectional radius greater than that of the core layer (3) in the initial state, the upper surface of the stress zone (2) in the final state and the upper surface of the glass substrate (1) are located on the same plane, the upper surface of the core layer (3) in the final state is located directly below the upper surface of the glass substrate (1) and are parallel to each other, the glass substrate (1) directly above the core layer (3) in the final state is the cladding (4), and finally the two electric field assisted ion exchange electrode plates (15) are removed.
6. The method for manufacturing a polarization-maintaining optical waveguide according to claim 1, characterized in that: In the step S4, the diameter of the stress zone (2) in the final state is 10 to 100 μm, and the diameter of the core layer (3) in the final state is 5 to 8 μm; the center distance between the stress zone (2) in the final state and the core layer (3) in the final state is greater than the sum of the radius of the core layer (3) in the final state and the radius of the stress zone (2) in the final state plus 10 μm, and the center distance between the stress zone (2) in the final state and the core layer (3) in the final state ranges from 18 to 75 μm; the thickness of the cladding (4) is 0.5 to 2 μm.
7. The method for manufacturing a polarization-maintaining optical waveguide according to claim 1, characterized in that: In the step S4, the refractive index of the core layer (3) in the final state is greater than the refractive index of the stress region (2) in the final state.
8. The method for manufacturing a polarization-maintaining optical waveguide according to claim 1, characterized in that: In the steps S1 and S2, the source ions of the first thermal ion exchange are Li + or K + The first thermal ion exchange time is 8 to 96 hours; the first electric field assisted exchange time is 3 to 10 minutes.
9. The method for manufacturing a polarization-maintaining optical waveguide according to claim 1, characterized in that: In the steps S3 and S4, the source ions of the second thermal ion exchange are Ag. + or Tl + The thermal ion exchange time is 5 to 30 minutes; the second electric field assisted exchange time is 15 to 120 minutes.
10. A polarization-maintaining optical waveguide, characterized in that: The polarization-maintaining optical waveguide is prepared by the method described in any one of claims 1-9.
